Adropin preserves the blood‐brain barrier through a Notch1/Hes1 pathway after intracerebral hemorrhage in mice. Issue 6 (17th November 2017) - Yu, Lingyan; Lu, Zhengyang; Burchell, Sherrefa; Nowrangi, Derek; Manaenko, Anatol; Li, Xue; Xu, Yang; Xu, Ningbo; Tang, Jiping; Dai, Haibin; Zhang, John H.
Abstract: Adropin is expressed in the CNS and plays a crucial role in the development of stroke. However, little is currently known about the effects of adropin on the blood‐brain barrier (BBB) function after intracerebral hemorrhage (ICH). In this study, the role of adropin in collagenase‐induced ICH was investigated in mice. At 1‐h post‐ICH, mice were administered with recombinant human adropin by intranasal. Brain water +content, BBB permeability, and neurological function were measured at different time intervals. Proteins were quantified using western blot analysis, and the localizations of adropin and Notch1 were visualized via immunofluorescence staining. It is shown that adropin reduced brain water content and improved neurological functions. Adropin preserved the functionality of BBB by increasing N‐cadherin expression and reducing extravasation of albumin. Moreover, in vivo knockdown of Notch1 and Hes1 both abolished the protective effects of adropin. Taken together, our data demonstrate that adropin constitutes a potential treatment value for ICH by preserving BBB and improving functional outcomes through the Notch1 signaling pathway. Abstract : Adropin is expressed in the central nervous system (CNS) and plays a crucial role in the development of stroke. In this study, the role of adropin in collagenase‐induced ICH was investigated in mice. Our research demonstrates that adropin constitutes a potential treatment value for ICH by preserving BBB and improving functional outcomes through the Notch1 signaling pathway.